Guarantee of Protection of Electronic Land Certificates as Proof of Ownership of Land Rights - Akbar Ramadhan Nugroho; Surya Anoraga; Esfandiari, Fitria (Indonesia Law Reform Journal, 2023)
Changes in information technology have an impact on the public service system, especially in the land sector which is experiencing a transition from Analog Certificates to Electronic Certificates which raises several challenges, one of which is in the field of law, in practice the power of law because electronic information and transactions cannot be used as evidence, but must meet certain requirements. The purpose of this research is to find out and analyze the legal force of Electronic Land Certificates and to find out the efforts made by the government to protect the Electronic Land Certificate system. The research method used is the Normative Juridical Approach. The results of this study are the legal protection of electronic certificates in proving that they have a position as legal electronic evidence have been recognized in the procedural law system in Indonesia, and have strong legal force. Electronic Land Certificates require a legal umbrella governing the use of Blockchain technology contained in the ITE Law to be delegated to an implementing regulation. This study concludes that Electronic Certificates have the same legal force as Analog Certificates. As an effort to support the use of Electronic Certificates, the government's role is needed in formulating laws that regulate the substance of the use of technology in electronic certificate database storage systems.